2019
DOI: 10.3892/ijmm.2019.4277
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Sonic hedgehog restores diabetic endothelial progenitor cells and improves cardiac repair after acute myocardial infarction in diabetic mice

Abstract: Damaged endothelial progenitor cells (EPCs) are associated with poor prognosis in diabetic myocardial infarction (DMI). Our previous studies revealed that an impaired Sonic hedgehog (Shh) pathway contributes to insufficient function in diabetic EPCs; however, the roles of the Shh pathway in diabetic EPC apoptosis under basal and hypoxic/ischemic conditions remain unknown. Therefore, the present study investigated whether Shh revitalized diabetic EPCs and consequently improved the deteriorative status of DMI. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…2B-2D). Previous studies have demonstrated that pro-inflammatory cytokines, such as interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α), serve as chemotactic factors for leukocytes to diabetic cardiac tissue [31,32]. T1DM cardiac tissue demonstrated a statistically significant increase in the expression of all these cytokines (1.5 ± 0.02 and 1.3 ± 0.07 fold increase, respectively).…”
Section: Dppi-ko Attenuates Stz Induced Cardiac Inflammationmentioning
confidence: 99%
“…2B-2D). Previous studies have demonstrated that pro-inflammatory cytokines, such as interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α), serve as chemotactic factors for leukocytes to diabetic cardiac tissue [31,32]. T1DM cardiac tissue demonstrated a statistically significant increase in the expression of all these cytokines (1.5 ± 0.02 and 1.3 ± 0.07 fold increase, respectively).…”
Section: Dppi-ko Attenuates Stz Induced Cardiac Inflammationmentioning
confidence: 99%
“…Treatment of EPC with different molecules such as thymosin beta-4 ( Poh et al, 2020 ) and the overexpression of Sonic hedgehog (Q. Xiao et al, 2019 ) recover the reparative properties of EPC after MI in the context of diabetes by inducing their mobilization (restoring their circulating levels) or promoting angiogenesis. Shexiang Baoxing pills -a traditional Chinese medicine for ischemic heart disease- causes this same effect of EPC mobilization and promotion of angiogenesis when there are no other co-morbidities, but its capacity to mobilize EPC post-MI in a diabetic context has not been studied yet ( Huang et al, 2017 ).…”
Section: New Insights Of Endothelial-mediated Protection Against Ischmentioning
confidence: 99%
“…Similarly, based on genetic lineage tracing analysis, in vivo experiments demonstrated that in a MI murine model, Bmi1 + progenitor cells resident in the heart underwent large proliferation and differentiation, resulting in de novo cardiac vasculature during post-MI ventricular remodeling, and depletion of these endothelial-related BMI1 + cells led to impaired angiogenesis and reduced ejection fraction, ultimately resulting in an ischemic-dilated cardiac phenotype [25] . BMI1 were also expressed in the diabetic endothelial progenitor cells (EPCs) and participated in diabetic myocardial infarction, experimental data showed that BMI1 was capable of mediating the antiapoptotic role of Shh pathway via inhibiting p53, and the activation of Shh/BMI1/p53 axis in diabetic EPCs markedly reduced EPC apoptosis and ameliorated EPC dysfunction, ultimately rescuing the diabetic myocardium under hypoxia [34] .…”
Section: Novel Roles Of Bmi1 In the Heartmentioning
confidence: 99%
“… endothelial progenitor cells BMI1 mediates the benefits of the Shh pathway by inhibiting p53 in diabetic EPCs. [34] cardiac oxidative stress High levels of ROS enforced BMI1 + cardiac progenitor differentiation. Cardiac BMI1 + cells made up 25% of the CM-committed cells, which had the highest ROS levels of all adult cardiac progenitor cells.…”
Section: Novel Roles Of Bmi1 In the Heartmentioning
confidence: 99%